LOTS and HOTS reading questions in EFL textbooks (Kurikulum Merdeka): unveiling every learning process purposes - Widiastuti, Maria Kartika; Mbato, Concilianus Laos (UNIB Press, 2025)
Higher-order thinking skills (HOTS) have received much attention in Indonesian English textbooks and research in recent years. However, the role of lower-order thinking skills (LOTS) is inevitable because it creates a stepping stone to reaching HOTS. The current research aimed to fill the gap of research in Bloom's taxonomy by demonstrating the function of LOTS to shape students' higher-order thinking skills in reading comprehension aside from another thinking category. Secondly, the research explored the implication of EFL Senior High School Texbooks’ (Kurikulum Merdeka) different characteristics represented in Bloom’s Taxonomy reading comprehension questions pattern. Each textbook has a different Bloom’s taxonomy question pattern. The second aims are inspired by research investigating Bloom's taxonomy, which mainly did not discuss English textbooks used in Kurikulum Merdeka. This research employed document analysis to investigate Bloom’s taxonomy in two Senior High School English textbooks. To triangulate the data analysis results, the researchers analyzed the answers to open-ended questions from two graduating undergraduate English education students. An experienced English teacher also verified the results of the analysis. The findings show that LOTS enabled students to pay attention to important details and the main ideas and apply the text structure. HOTS enhanced critical thinking, problem-solving, strategic thinking, empathy, and creativity. LOTS and HOTS questions should be complementary to empower students’ reading skills. The findings provide insights into the nuance in reading comprehension through the balanced structure of LOTS and HOTS questions.